Loading path and strain rate effects on the deformation behavior of [0001] textured nanocrystalline magnesium: An atomic-scale investigation - Hui Zhao; Xuejian Yang; Yan Peng; Lu Wu; Yu Wu; Baodong Shi (Journal of Magnesium and Alloys)
Molecular dynamics (MD) simulation is employed to investigate the deformation behavior under various loading paths and strain rates of nanocrystalline magnesium (NC Mg) with [0001] texture. Atomic-scale structural evolution of NC Mg was performed under uniaxial and biaxial loadings. In tension process, compression twins and basal slip dominate, while the compression process is dominated by tension twins. The activation mechanism of twinning is highly sensitive to the loading path and grain orientation. Meanwhile, the effect of strain rate on the structural evolution of NC Mg was investigated. It is found that the effect of strain rate on the plastic deformation of NC Mg is reflected through the plasticity delays and the way to release the stress. As the strain rate decreases, the plastic deformation mechanism gradually changes from intragranular to grain boundary. Some significant potential deformation mechanisms in the loading process were studied. It is observed that {112¯1} twins nucleated inside the grains, and the thickening process is completed by basal 〈a〉 slip of the twin boundary. The strain compatibility between twins is automatically optimized with loading. Moreover, the detwinning mechanism caused by the interaction between twins and basal stacking faults is clarified.